2018
DOI: 10.3802/jgo.2018.29.e57
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, practice and barriers of cervical cancer screening among women living in mid-western rural, Nepal

Abstract: ObjectiveTo find out the knowledge, attitude, practice, and barriers of cervical cancer screening in mid-western rural, Nepal.MethodsA hospital-based cross-sectional study was conducted. Women aged 20 or more were interviewed using a structured questionnaire regarding the socio-demographic information, knowledge, attitude, practice, and barriers to the cervical cancer screening.ResultsTotal of 360 participants were recruited for this study, mean age was 30.13±10.4 years. More than 87% of participants had inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
84
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 18 publications
13
84
4
4
Order By: Relevance
“…Moreover, women were found to have favourable attitude despite the poor knowledge and practices towards cervical cancer prevention in our study. This finding is consistent with the result of studies done by Bansal et al from Bhopal and Shreshta et al and Thapa et al from Nepal [17,29,32].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, women were found to have favourable attitude despite the poor knowledge and practices towards cervical cancer prevention in our study. This finding is consistent with the result of studies done by Bansal et al from Bhopal and Shreshta et al and Thapa et al from Nepal [17,29,32].…”
Section: Discussionsupporting
confidence: 94%
“…The majority of participants were aged 25-38 years, married, with secondary school level of education and had formal activity. Similar study in Nepal reported a majority of participants in the age group of 20-29 years who were married and had a secondary level of education or more (Thapa et al, 2018). Most of the participants were at the reproductive age which might be a reason for the large participation in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Second, the barriers to cervical cancer screening identified from the study are feeling well or having no symptoms at all and the fear of embarrassment that results from showing their private parts to the health professionals. In addition to this, other studies in Nepal identified illiteracy [6,10,11], lack of awareness about cervical cancer and its screening methods, embarrassment, having no symptoms at all [12,13], fear of finding out cancer [8], sociocultural barriers, service providers’ behavior, geographical challenges, poor financial condition [13] as a significant barrier to cervical cancer screening uptake behavior, while living in a rural area [11], participating in awareness program, support from family and women’s group [13] act as a facilitator to increase the screening uptake in women. Similarly, a cross-sectional study in Morocco also reported poor awareness in women about cervical cancer and have no symptoms at all as a cause for poor Pap screening uptake practice [14].…”
Section: Discussionmentioning
confidence: 96%